2020
DOI: 10.1101/2020.11.10.20229005
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-occupational and occupational factors associated with specific SARS-CoV-2 antibodies among Hospital Workers – a multicentre cross-sectional study

Abstract: Background Protecting healthcare workers (HCW) from Coronavirus Disease-19 (COVID-19) is critical to preserve the functioning of healthcare systems. We therefore assessed seroprevalence and identified risk factors for Severe Acute Respiratory Syndrome-Coronavirus-2 (SARS-CoV-2) seropositivity in this population. Methods Between June 22nd and August 15th 2020, employees from healthcare institutions in Northern/Eastern Switzerland were screened for SARS-CoV-2 antibodies. We recorded baseline characteristics,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 39 publications
(53 reference statements)
5
23
1
Order By: Relevance
“…age, sex, profession) were similar between the total HCW population (from the largest participating institution) and the cohort population. 20 To conclude, FFP2 use outside of AGPs is associated with a reduced risk of SARS-CoV-2 acquisition for HCW with high COVID-19 exposure, while those with only sporadic or no known contact do not seem to benefit. The effect size should be interpreted in the context of the global COVID-19 risk for HCW, which is driven by exposure to positive household contacts.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…age, sex, profession) were similar between the total HCW population (from the largest participating institution) and the cohort population. 20 To conclude, FFP2 use outside of AGPs is associated with a reduced risk of SARS-CoV-2 acquisition for HCW with high COVID-19 exposure, while those with only sporadic or no known contact do not seem to benefit. The effect size should be interpreted in the context of the global COVID-19 risk for HCW, which is driven by exposure to positive household contacts.…”
Section: Discussionmentioning
confidence: 88%
“…Employees registered online and provided electronic consent. Enrolment took place from June 22 nd to August 15 th 2020, between the end of the first COVID-19 wave in Switzerland and the surge of the second wave; 20 data were analysed up to March 9 th 2021, when the second wave had abated ( Figure 1 ). The study was approved by the ethics committee of Eastern Switzerland (#2020-00502).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the beginning of the pandemic, several studies have investigated the risk for HCW for infections with SARS-CoV-2. While some studies showed low infection rates among HCW indicating that the implemented protection measures were effective, (1)(2)(3)(4) others studies revealed high infection rates among HCW (5)(6)(7)(8)(9)(10)(11). The most frequently identi ed risk factors for transmission of SARS-CoV-2 to HCW include working at dedicated COVID-19 units (6, 7), having either direct contact with infected patients (8,9), or infected co-workers (9,11) and being exposed to infected household members(8, 10,11).…”
Section: Introductionmentioning
confidence: 99%